2010
DOI: 10.1186/1471-227x-10-17
|View full text |Cite
|
Sign up to set email alerts
|

A concept for major incident triage: full-scaled simulation feasibility study

Abstract: BackgroundEfficient management of major incidents involves triage, treatment and transport. In the absence of a standardised interdisciplinary major incident management approach, the Norwegian Air Ambulance Foundation developed Interdisciplinary Emergency Service Cooperation Course (TAS). The TAS-program was established in 1998 and by 2009, approximately 15 500 emergency service professionals have participated in one of more than 500 no-cost courses. The TAS-triage concept is based on the established triage Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Further, only 56% of the EMS responders had access to triage tagging equipment, indicating a need for standardised solutions for triage and marking of priority [22]. Experience from the terrorist bombings in London showed that advanced pre-hospital skills improved triage accuracy [13]; however before such skills are available, simple concepts may improve the precision and speed of the triage process [26], as well as rationalise the evacuation of patients and the interdisciplinary cooperation at the scene of the accident [27]. The inquiry after the avalanche disaster in Vassdalen recommended the introduction of more stringent communication routines, better availability of rescue dogs and better avalanche response equipment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Further, only 56% of the EMS responders had access to triage tagging equipment, indicating a need for standardised solutions for triage and marking of priority [22]. Experience from the terrorist bombings in London showed that advanced pre-hospital skills improved triage accuracy [13]; however before such skills are available, simple concepts may improve the precision and speed of the triage process [26], as well as rationalise the evacuation of patients and the interdisciplinary cooperation at the scene of the accident [27]. The inquiry after the avalanche disaster in Vassdalen recommended the introduction of more stringent communication routines, better availability of rescue dogs and better avalanche response equipment [28].…”
Section: Discussionmentioning
confidence: 99%
“…The post-disaster environment set up in this type of exercises approximates comprehensive field conditions [12] as close to a realistic intervention as possible [13]. Such realistic environment allows trainings to provide valuable results [14]. Field exercises comprise a series of events and a group of stakeholders.…”
Section: Disaster Exercisesmentioning
confidence: 99%
“…& Restoration of health care infrastructure through a seismically safe and rationalised health care system & Practising continuous integrated triage in the disaster fields and subsequently in the hospitals to treat the maximum with whatever resources are at hand [18,19] & Providing an integrated health care delivery system covering preventive, curative and rehabilitation services ORIF open reduction and internal fixation & Strengthening the health services through revival of the management and organisational system…”
Section: Discussionmentioning
confidence: 99%